2021
DOI: 10.21070/perisai.v5i2.1532
|View full text |Cite
|
Sign up to set email alerts
|

The Persepsi Masyarakat Terhadap Destinasi Wisata Syariah: Tujuan Fenomena (Studi Kasus Pada Wisata Syariah Utama Raya Banyuglugur Situbondo)

Abstract: Wisata syariah merupakan wisata yang mengedepankan nilai dan norma keislaman yang sesuai dengan syariat islam sebagai landasan dasarnya. Penelitian ini bertujuan untuk mengetahui atau melihat bagaimana persepsi masyarakat atau wisatawan terhadap destinasi wisata syariah di Utama Raya Banyuglugur Situbondo. Penelitian ini merupakan penelitian kuantitatif dengan metode survey yang dilakukan dengan menyebarkan kusioner terhadap 55 responden. Hasil penelitian ini menunjukkan bahwa wisatawan dan masyarakat setempat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
2
0
2
Order By: Relevance
“…The coefficient value on the perception variable is 0.325, meaning that if public perception increases, it will increase the development of halal tourism by 0.325.The results of this study are also in line with researchSaifuddin and Mukarromah (2021) His research explains the good public perception of the application of sharia tourism. Creating a good public perception will make Indonesia an attractive sharia tourism destination.In addition,Fawaid and Khotimah (2019) in their research, they found that public perception of sharia tourism was positive, namely 75%.…”
supporting
confidence: 82%
“…The coefficient value on the perception variable is 0.325, meaning that if public perception increases, it will increase the development of halal tourism by 0.325.The results of this study are also in line with researchSaifuddin and Mukarromah (2021) His research explains the good public perception of the application of sharia tourism. Creating a good public perception will make Indonesia an attractive sharia tourism destination.In addition,Fawaid and Khotimah (2019) in their research, they found that public perception of sharia tourism was positive, namely 75%.…”
supporting
confidence: 82%
“…7 No. 1 Januari -Juni 2023: 42 -56 Suwarno,Uswatun Chasanah,Muchamad Suradji,Ahmad Yunus Mokoginta Harahap | 46 Islamic shari'ah as its primary foundation (Saifuddin & Mukarromah, 2021). Currently, the tourism industry is indeed dominated by tourists who only pursue financial gain.…”
Section: Review Of Sharia Tourismmentioning
confidence: 99%
“…Rares, 2021). Memberikan kemudahan bagi pemerintah, pengusaha dan masyarakat untuk memenuhi kebutuhan wisatawan inbound (Saifuddin, 2021). Pariwisata merupakan sektor ekonomi yang dapat menghasilkan pendapatan daerah dan aliran pendapatan bagi masyarakat sekitar.…”
Section: Pendahuluanunclassified